IMPLEMENTASI FUSION FOOD PADA MAKANAN TRADISIONAL UNTUK MENINGKATKAN MINAT BELAJAR MAHASISWA SENI KULINER - Nur Wahyuni (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2022)
Innovation in the field of processed food combines several elements of different culinary traditions from 2 or more countries to create a new cuisine with a more innovative taste called Fusion Food. This processed food can display a portion of food in various types; processed food combines processed foods from several countries or regions to make it look artistic but still have a distinctive taste. This study aims to provide an overview and motivation to AKS AKK Yogyakarta culinary arts students to be more interested in learning culinary arts, mainly traditional cuisine. This research uses qualitative methods. The qualitative methodology used in this research is an analytical descriptive study. The research subjects in this study were AKS AKK students of the Culinary Arts Study Program. The data collection methods used are observation, interviews, and documentation. The data analysis techniques used in this study were male and Huberman techniques. Data analysis techniques include data reduction, data presentation, and concluding. Data validation using triangulation techniques. Based on the analysis and discussion results, it can be supposed that 1. The application of Fusion Food can motivate AKS AKK students to creatively preserve traditional food while maintaining and strengthening character based on local wisdom. 2. The application of fusion food can be used as an alternative way of developing traditional food practice learning models to be more interested in learning culinary arts in a contextual and meaningful manner so that graduates become competent. 3. This fusion food dish can also be an approach to introducing Indonesian food to the millennial generation so that they can love traditional food.